La maduración de frutos en árboles aislados de Acnistus arborescens (Solanaceae) redirige la dispersión de semillas por aves en un parque urbano costarricense: None (Repertorio Científico, 2026)
“Fruit ripening on isolated Acnistus arborescens (Solanaceae) trees redirects seed dispersal by birds in a Costa Rican urban park”. Seed dispersal is a key factor in natural regeneration and occurs in all types of green areas, even those surrounded by urban development, where research on this topic is scarce. Objective: To compare ornithochory in three microsites of an urban park: lawn, forest edge and under isolated Acnistus arborescens trees, considering ecological, phenological and climatic aspects. The methodology adopted was quantitative, with a quasi-experimental design and comparative approach: we carried out two samplings per month for twelve consecutive months, placing twenty seed traps (0.71 m x 0.71 m) in each microsite to quantify dispersion and analyze germination. As a result, we detected more excrement during the rainy season and under isolated trees with ripe fruit. The amount of excreted and free seeds did not differ between seasons or microsites, but accumulated under trees with ripe fruit. Dispersed species richness, diversity, and dominance were higher at the forest edge. Seed abundance was higher under isolated trees. Germination percentage did not differ between treatments. The variable "fruit ripening" showed an effect on the quantity of bird droppings. The variables "phenological stage," "wind," and "fruit ripening" showed an effect on seed dispersal in bird droppings. In conclusion, our research indicates that the density of dispersed droppings and seeds increases with the presence of ripe fruit on isolated trees, and that the diversity of dispersed plant species remains high at the forest edge. The ecological patterns studied are applicable to the ecological restoration of urban ecosystems.